2021
DOI: 10.1515/ijnes-2021-0060
|View full text |Cite
|
Sign up to set email alerts
|

Depression, anxiety and stress among Australian nursing and midwifery undergraduate students during the COVID-19 pandemic: a cross-sectional study

Abstract: Objectives To assess depression, anxiety and stress among undergraduate nursing and midwifery students during the COVID-19 pandemic, and identify socio-demographic and educational characteristics associated with higher depression, anxiety and stress scores. Methods Cross-sectional study during August–September 2020, using an anonymous, online, self-administered survey. E-mail invitations with a survey link were sent to 2,907 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 37 publications
2
23
2
1
Order By: Relevance
“…Healthcare workers in the private sector had a higher turnover intention than those in the public sector. In contrast with current study, the effects of gender, education level, and work level on turnover intention were not significant ( Yáñez et al, 2020 ).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Healthcare workers in the private sector had a higher turnover intention than those in the public sector. In contrast with current study, the effects of gender, education level, and work level on turnover intention were not significant ( Yáñez et al, 2020 ).…”
Section: Discussioncontrasting
confidence: 99%
“…In the Magnavita et al (2021) study conducted in two COVID-19 hub hospitals in central Italy with intensive care physicians, the results showed that a total of 21% of participants were dissatisfied with their job and 41.2% said they intended to quit ( Magnavita et al, 2021 ). Yáñez et al (2020) conducted a cross-sectional survey to assess the anxiety, distress, and turnover intention of healthcare workers in Peru during the COVID-19 pandemic. Of the 303 healthcare workers, 53 were physicians, 63 were nurses, 63 were pharmacists, 80 were technicians, 20 were volunteers, and 24 were others.…”
Section: Discussionmentioning
confidence: 99%
“…As our findings indicate, it is more crucial than ever to explore the impact of COVID-19 on nurses' and nursing students' use of grit and positive thinking, as rates of nurse suicide and self-harm have increased during the pandemic ( Gao et al, 2021 ). Additionally, reports of stress, anxiety, and depression were reported among Saudi nursing students ( Alsolais et al, 2021 ) and non-Saudi nursing students ( Gao et al, 2021 ; Wynter et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic marked a significant increase in the degree of stress, anxiety, and depression in students of nursing (Espina-López et al, 2021; Savitsky et al, 2020; Tanji and Kodama, 2021; Wynter et al, 2021). In connection with the declining number of students and the global shortage of nurses, this may be a significant phenomenon requiring a more rigorous analysis (Melo et al, 2010).…”
Section: Introductionmentioning
confidence: 99%